Teacher Practices in Translanguaging and Trans-semiotizing pedagogy in ELT classrooms: An Indonesian Case Study - Sartika sri Rahayu; Dewi Rochsantiningsih; Sumardi Sumardi (Universitas Hamzanwadi, 2023)
Translanguaging and trans-semiotizing are emerging as pivotal methodologies in modern English teaching. The way a teacher adopts these methods is of paramount importance, especially when considering the combination of native language usage and multimedia resources which can profoundly influence the learning curve of English as a second language. This research delves into the practical application of these techniques in English Language Teaching (ELT) and their inherent benefits. Chosen through a purposive sampling technique based on their duration of English teaching experience (5 to 10 years), three educators from junior high schools in Indonesia were included in the study. Using interviews and classroom observation as primary data sources, a thematic analysis was conducted. The results highlight teachers' inclination towards translation tactics, like translating and code-switching, to foster student engagement. The analysis reveals teachers' proclivity towards utilizing methods such as translating and code-switching to enhance classroom interaction. Additionally, the embracing of trans-semiotization resources, spanning from simple hand gestures to advanced digital materials like videos and online links, stands out as a dominant feature in their pedagogy. This study enhances the existing discourse on translanguaging, offering tangible recommendations for language-teaching stakeholders.